2020
DOI: 10.1038/s41560-020-00719-z
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of descriptive and injunctive social norms in promoting energy conservation

Abstract: Inclusion in the sample is based exclusively on technical eligibility criteria set by the utility: households must have a valid name and email address as of June 2016, live in single-family homes, have at least one year of valid pre-experiment energy consumption data, have no negative electricity meter reads, at least one meter read in the previous three months, no significant gaps nor extreme peaks in usage history, and exactly one account per customer per location. While these criteria may result in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 55 publications
(79 reference statements)
3
17
0
Order By: Relevance
“…This may be because water consumption in the UK is generally lower than that found in the US and Colombia, so there is less scope for improvement. This is similar to the findings in energy-focused interventions, that effect sizes in Europe are smaller than those in the US, due to the lower energy consumption in Europe [24,25]. The average water consumption of an individual living in the US is around 400 L per day, whereas in the UK it is 141 L per day.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This may be because water consumption in the UK is generally lower than that found in the US and Colombia, so there is less scope for improvement. This is similar to the findings in energy-focused interventions, that effect sizes in Europe are smaller than those in the US, due to the lower energy consumption in Europe [24,25]. The average water consumption of an individual living in the US is around 400 L per day, whereas in the UK it is 141 L per day.…”
Section: Discussionsupporting
confidence: 85%
“…The intervention was found to reduce household energy consumption by around 2.2%. The intervention has since been conceptually replicated across other countries but was found to have smaller effect sizes in Germany [24] and Italy [25]. Similarly, this approach has also effectively reduced household water consumption by around 4% in the US and Colombia [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical cooperators respond positively to what they expect others to do while threshold-driven respond negatively to their empirical expectations; normative expectation-driven cooperators and social norm followers respond positively to an increase in normative expectations. This implies policy making must embrace heterogeneity, designing interventions that reach all types based on both empirical and normative expectations and avoiding potentially harmful messages that focus only on empirical affairs that may backfire for some individuals (threshold types in our context) 34 . Finally, we have shown that a precise, measurable definition of social norm allows quantitative analyses lead to insights about the feedbacks between norms and behavior, leading in turn to specific predictions of optimal behavioral change interventions relevant to global societal challenges.…”
Section: Discussionmentioning
confidence: 99%
“…This estimated mitigation wedge is conservative. The reductions could be enhanced by using our evidence on interactions between the various interventions, including the consideration of interaction between injunctive and descriptive norms 45 , and the interaction between social norms, behavioral interventions and infrastructure provisions or building design 47 . Cost effectiveness of a basket of interventions should also be assessed by taking into account the costs of different interventions (monetary incentives for example could entail higher infrastructure and regulatory costs).…”
Section: Discussion and Outlookmentioning
confidence: 99%